Resources and the application of Soft Power tools in Foreign Policy of Kazakhstan - Kuramayeva, Г. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
This paper aims to explore main resources of “soft power” of Kazakhstan, which is an important political tool in modern world politics. Evaluation and analysis of the advantages and disadvantages of the policy conducted by Kazakhstan “soft power” as well as the adjustment on its basis of its foreign policy orientations and priorities there is a requirement of time. This is especially important for Kazakhstan, which is the leading country in the Central Asian region. The author in this article tried to analyze the “soft power” of Kazakhstan’s diplomacy and foreign policy. Moreover was showed attempts how and where can Kazakhstan to use “soft power” tools. The purpose of the article is not an answer to the questions has Kazakhstan “soft power”? If there is, is it systemic? How effective is it? All these questions are voluminous. The goal is also not to review the entire soft power tool that is or can be applied by Kazakhstan. The purpose of this research is to show only those instruments of “soft power” of Kazakhstan that can be used “here and now”, relatively economically not costly, but at the same time - effective. For the successful implementation of “soft power”, Kazakhstan needs to more actively implement soft power tools, first of all, in the Central Asian region. It is necessary to concentrate on creating by Kazakhstan a zone of goodneighborliness and friendship in Central Asia, through tools of “soft power”.